2001
DOI: 10.1055/s-2001-14071
|View full text |Cite
|
Sign up to set email alerts
|

Vasospasms Are Characteristic in Cases with Eclampsia/Preeclampsia and HELLP Syndrome: Proposal of an Angiospastic Syndrome of Pregnancy

Abstract: We attempted to prove the occurrence of generalized vasospasms in cases with eclampsia/preeclampsia and HELLP syndrome and to suggest the existence of an angiospastic syndrome of pregnancy. Sixteen cases with severe preeclampsia were evaluated. Among them, three cases were complicated by eclampsia and one case with HELLP syndrome. Cranial magnetic resonance angiography (MRA) was performed in 15 cases, and celiac angiography was performed in one case. Vasospasms were observed in 12 cases (75.0%), including all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 17 publications
0
26
0
2
Order By: Relevance
“…Based on their experiments they put forward the hypothesis that preeclampsia might be an 'NO deficiency disease'. A group of researchers from Japan led by Kobayashi et al [26] suggested that preeclampsia and the HELLP syndrome might be clinical manifestations of a 'vasospastic syndrome of pregnancy'. They had observed cerebral and peripheral vasospasms in 12 out of 15 preeclamptic women who were investigated by nuclear magnetic resonance imaging.…”
mentioning
confidence: 99%
“…Based on their experiments they put forward the hypothesis that preeclampsia might be an 'NO deficiency disease'. A group of researchers from Japan led by Kobayashi et al [26] suggested that preeclampsia and the HELLP syndrome might be clinical manifestations of a 'vasospastic syndrome of pregnancy'. They had observed cerebral and peripheral vasospasms in 12 out of 15 preeclamptic women who were investigated by nuclear magnetic resonance imaging.…”
mentioning
confidence: 99%
“…Headache character (throbbing or pounding) and other associated symptoms described by most of these women (blurring of vision, photophobia, sonophobia, nausea, vomiting) are similar to the headaches described in patients with migraine without aura [11]. This is an interesting observation, as eclampsia is considered to be a multisystem vascular syndrome by many and vascular changes as evidenced by four vessel cerebral angiogram, magnetic resonance angiogram (MRA) and transcranial Doppler (TCD) studies provide evidence for the same [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 78%
“…With the basic pathological change of systemic small vessel spasm, PE often involves multiple organs [36]. Our study showed that PE patients had higher serum levels of ALT, AST, urea nitrogen, creatinine and uric acid compared to controls, which revealed that PE is often accompanied by impaired liver and renal functions.…”
Section: Discussionmentioning
confidence: 80%